Analysis of Promotion Strategy and Packaging Design on Repurchase Intention (AIDA Implementation) - Shendri, Gabriella Natasha; Arimbawa, Putu Adi Putra (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Purpose –    This study aims to examine the influence of promotion strategy and packaging design on consumers' repurchase intention in MyPaw Mart, an Indonesian SME producing organic and human-grade cat treats, by applying the AIDA (Attention, Interest, Desire, and Action) framework.   Design/methodology/approach –  This study employs a quantitative research approach using survey data collected from MyPaw Mart consumers. The relationships among promotion strategy, packaging design, and repurchase intention were analyzed based on the AIDA framework to evaluate the effects of marketing activities on consumer purchasing behavior.   Findings – The results indicate that both promotion strategy and packaging design have a positive and significant influence on consumers' repurchase intention. Effective promotional activities, including engaging social media campaigns and attractive discount programs, successfully increase consumer attention and desire. Furthermore, packaging that is visually appealing and clearly communicates product information enhances consumer trust, thereby encouraging repeat purchase decisions.   Originality/value – This study contributes to the growing literature on SME marketing in emerging markets by extending the application of the AIDA model to the pet food industry. It also provides practical insights for SMEs on improving customer retention through effective promotion strategies and informative packaging design.